Digital cognitive training in children with attention-deficit/hyperactivity disorder: a study protocol of a randomised controlled trial - Sally Richmond; Hannah Kirk; Kim Cornish; Mark A Bellgrove; Tori Gaunson; Meg Bennett (BMJ Open, 2022)
Introduction Attention-deficit/hyperactivity disorder (ADHD) is one of the most prevalent neurodevelopmental disorders and is a persistent pattern of inattention and/or hyperactivity-impulsivity that interferes with daily functioning. Children with ADHD are developmentally vulnerable, with the disorder linked to emotional regulation difficulties, behavioural disturbances, as well as academic challenges. Emerging evidence suggests that children with ADHD may benefit from cognitive training interventions, including those focused on attention. This study aims to assess the immediate and long-term efficacy of an attention training intervention in children with ADHD.Methods and analysis This study is a preregistered, parallel, double blind, randomised controlled trial. Participants will comprise 104 children with a diagnosis of ADHD aged 5–8 years 11 months. Participants will be randomly allocated to either an adaptive, digital game-based (1) attention training programme (intervention) or (2) a numeracy programme (control). Both programmes will be delivered on a touchscreen tablet, and children will complete five 20 min sessions per week for a 5-week period at home (25 sessions in total). Assessments of the primary outcome (ie, attention and inhibitory control) and secondary outcomes (ie, selective attention, interference control, sustained attention, inhibition, behavioural attention, impairment in everyday functioning, working memory and executive functioning) will occur at preintervention, immediately postintervention and at 3-month follow-up. Multivariate linear regression will be employed to examine primary and secondary outcomes. The data analyst will be blinded to group membership.Ethics and dissemination Ethics approval has been obtained from the Monash University HREC (20495). Results will be disseminated through peer-reviewed journals, conference presentations, media outlets, the internet and various community/stakeholder activities.Trial registration number ACTRN12620000964910, UTN U1111-1250-2620.